Hubungan komunikasi terapeutik terhadap pelayanan kesehatan gigi dan mulut - Herry Imran; Niakurniawati Niakurniawati; Nasri Nasri (Poltekkes Kemenkes Aceh, 2023)
Background: Patient dissatisfaction is caused by the care and services provided not being able to meet the patient's needs. Therapeutic communication in dental and oral health services at the Batoh Health Center in Banda Aceh is often discussed by patients who visit daily.Objective: The study aims to determine the relationship between the therapeutic communication of dental health workers and patient satisfaction with oral health services.Method: The research design used cross-sectional, conducted at the Batoh Health Center, Banda Aceh City in December 2021. The sample was 32 patients who visited the Batoh Health Center Dental Clinic, taken by accidental sampling. Data collection by observation and interview using a questionnaire instrument. Bivariate data analysis through Chi-Square statistical test, at 95% CI.Results: This shows that dental nurses' therapeutic communication when providing services is good (80,0%), and the satisfaction level of visiting patients is 53,1%. There is a relationship between the therapeutic communication of dental health workers and the level of satisfaction of patients visiting the Batoh Health Center Dental Clinic, Banda Aceh City (p = 0,029).Conclusion: Therapeutic communication is related to the satisfaction level of patients visiting the Batoh Health Center Dental Clinic, Banda Aceh City.